Relations between the loop transposition of DNA G-quadruplex and the catalytic function of DNAzyme - Cheng, Mingpan; Zhou, Jun; Jia, Guoqing; Ai, Xuanjun; Mergny, Jean-Louis; Li, Can (Biochimica et biophysica acta. General subjects, 2017)
The structures of DNA G-quadruplexes are essential for their functions in vivo and in vitro. Our present study revealed that sequential order of the three G-quadruplex loops, that is, loop transposition, could be a critical factor to determinate the G-quadruplex conformation and consequently improved the catalytic function of G-quadruplex based DNAzyme. In the presence of 100mM K+, loop transposition induced one of the G-quadruplex isomers which shared identical loops but differed in the sequential order of loops into a hybrid topology while the others into predominately parallel topologies. 1D NMR spectroscopy and mutation analysis suggested that the hydrogen bonding from loops residues with nucleotides in flanking sequences may be responsible for the stabilization of the different conformations. A well-known DNAzyme consisting of G-quadruplex and hemin (Ferriprotoporphyrin IX chloride) was chosen to test the catalytic function. We found that the loop transposition could enhance the reaction rate obviously by increasing the hemin binding affinity to G-quadruplex. These findings disclose the relations between the loop transposition, G-quadruplex conformation and catalytic function of DNAzyme.
Keywords: Hydrogen Bonding; G-quadruplex ligand; DNAzyme; hemin; biokatalýza; DNA katalytická; G-kvadruplexy; vodíková vazba; G-Quadruplexes; Biocatalysis; Loop transposition; DNA, Catalytic; Hemin; DNA catalysis; G-quadruplex